2023
DOI: 10.1136/rapm-2023-104568
|View full text |Cite
|
Sign up to set email alerts
|

Cooled radiofrequency ablation versus standard medical management for chronic sacroiliac joint pain: a multicenter, randomized comparative effectiveness study

Abstract: IntroductionLow back pain is the leading cause of disability worldwide, with sacroiliac joint pain comprising up to 30% of cases of axial lower back pain. Conservative therapies provide only modest relief. Although placebo-controlled trials show efficacy for sacral lateral branch cooled radiofrequency ablation, there are no comparative effectiveness studies.MethodsIn this randomized, multicenter comparative effectiveness study, 210 patients with clinically suspected sacroiliac joint pain who obtained short-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Considering this, CRT emerges as a therapeutic option with greater effectiveness and a lower risk of severe adverse effects. This technique has been shown to offer statistically superior improvements across the spectrum of patients with chronic sacroiliac joint pain [29], intercostal neuralgia, knee osteoarthritis, discogenic lower back pain [30], and other painful conditions compared to standard medical management. Generally, the improvement of pain by CRT is obtained by ablating the nerves that give rise to the unpleasant sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this, CRT emerges as a therapeutic option with greater effectiveness and a lower risk of severe adverse effects. This technique has been shown to offer statistically superior improvements across the spectrum of patients with chronic sacroiliac joint pain [29], intercostal neuralgia, knee osteoarthritis, discogenic lower back pain [30], and other painful conditions compared to standard medical management. Generally, the improvement of pain by CRT is obtained by ablating the nerves that give rise to the unpleasant sensation.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of RFA treatments of the SI joint is demonstrated by numerous observational, [88][89][90] retrospective, [91][92][93] and randomized controlled studies. 58,[94][95][96][97][98][99][100] However, the selection criteria, definitions of success, RFA techniques (conventional monopolar, bipolar, multielectrode combination mono-and bipolar, and monopolar cooled), and parameters (ie, temperature, duration, and location of RFA treatment), and imaging techniques (fluoroscopy, CT, ultrasound) have varied widely between studies.…”
Section: Extra-articular and Combination Injectionsmentioning
confidence: 99%
“…At the 3-month primary endpoint, 47% of patients in the RFA group experienced a positive outcome, defined as ≥50% reduction in average pain coupled with significant improvement in either the SF-36 bodily pain score or functional capacity measured by Oswestry disability index, versus 12% in the control group. In their most recent multi-center randomized controlled study involving 210 patients who responded with short-term relief to SI joint injections and experienced significant benefit with prognostic lateral branch blocks, Cohen et al 100 reported the superiority of the cooled RFA over standard medical management, with 52% of patients in the RFA group experiencing a positive categorical outcome at the 3-month endpoint versus only 4% in the control group.…”
Section: Extra-articular and Combination Injectionsmentioning
confidence: 99%
See 1 more Smart Citation